2005
DOI: 10.1128/cdli.12.10.1243-1245.2005
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of an Intranasally Administered Modified Live Canine Parvovirus Type 2b Vaccine in Pups with Maternally Derived Antibodies

Abstract: The ability of a modified live canine parvovirus type 2b vaccine to elicit active immunization in pups with maternally derived antibodies (MDA) by intranasal administration was evaluated. The vaccine induced seroconversion in 100% of pups with MDA titers of <80 and in 51.6% of pups with titers between 160 and 320.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 34 publications
1
42
0
2
Order By: Relevance
“…There have been concerns expressed over the efficacy of canine parvovirus vaccines which are based on the original type 2 strain [49,91]. The reports of gastroenteritis subsequent to vaccination are related to infection with CPV field strains shortly before or after the vaccine administration [23].…”
Section: Immunizationmentioning
confidence: 99%
“…There have been concerns expressed over the efficacy of canine parvovirus vaccines which are based on the original type 2 strain [49,91]. The reports of gastroenteritis subsequent to vaccination are related to infection with CPV field strains shortly before or after the vaccine administration [23].…”
Section: Immunizationmentioning
confidence: 99%
“…They speculated that high titre MLV vaccines might be superior to others. In independent studies, other researchers concluded that seroconversion rates attained in their studies despite high MDA were dose related (Burtonboy et al, 1991;Hoare et al, 1997;Martella et al, 2005). Nevertheless, the titre in a vaccine may be meaningless if the minimum protective dose is not known (Appel, 1999), suggesting that over-attenuated virus may have a high titre in tissue culture but may not be adequately immunogenic.…”
Section: Discussionmentioning
confidence: 99%
“…It thus follows that it may be prudent to vaccinate pups in infected breeding kennels at four weeks of age, rather than the standard six weeks in order to shorten the window of susceptibility. Factors that may affect the magnitude of the post-vaccinal immune responses to CPV vaccines are the vaccine virus titre, the degree of virus attenuation, the antigenic properties of the vaccine strain and the route of administration (Martella et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…CPV2a and CPV2b, which were identified in year 1979 and 1984, respectively (Shackelton et al, 2005). Most of the dogs are infected by above two strains (Martella et al, 2005 …”
Section: Introductionmentioning
confidence: 99%